2015
DOI: 10.1136/jnnp-2014-310181
|View full text |Cite
|
Sign up to set email alerts
|

Hospital revisit rate after a diagnosis of conversion disorder

Abstract: CD is associated with a substantial hospital revisit rate. Our findings suggest that CD is not an acute, time-limited response to stress, but rather that CD is a manifestation of a broader pattern of chronic neuropsychiatric disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Therefore, the interventions and any information or explanation received during inpatient admission did not reduce future acute healthcare utilization in our cohort. It is known that acute healthcare demand can respond sharply to appropriate explanation of the diagnosis of functional seizures [13,14], but this does not appear to have extrapolated to our cohort of patients with mixed FND, a finding consistent with behaviours in similar populations [15,16]. Lack of psychological support and intervention is a potential cause, even if the therapeutic effect of psychological interventions remains poorly understood (see below).…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, the interventions and any information or explanation received during inpatient admission did not reduce future acute healthcare utilization in our cohort. It is known that acute healthcare demand can respond sharply to appropriate explanation of the diagnosis of functional seizures [13,14], but this does not appear to have extrapolated to our cohort of patients with mixed FND, a finding consistent with behaviours in similar populations [15,16]. Lack of psychological support and intervention is a potential cause, even if the therapeutic effect of psychological interventions remains poorly understood (see below).…”
Section: Discussionmentioning
confidence: 78%
“…Approximately 20%–30% of patients at neurological clinics suffer from CD/FND (Stone et al, ; Aybek et al, ; Feinstein, ). CD/FND occurs mostly in the 2nd–4th decade and generally takes a protracted course with high limitations in general, social and work functioning in addition to high medical healthcare utilization (Merkler et al, ). Family members also feel a burden (Griffith, Polles, & Griffith, ) as patients with CD/FND often need long‐time intensive help, can become dependent on a wheelchair, and may need adaptations of their house and living arrangements.…”
Section: Introductionmentioning
confidence: 99%
“…As treatment may have relatively little to offer, family members often provide care. Patients with CD/FND visit neurological wards for diagnostic procedures (Stone & Vermeulen, 2016;Vermeulen & Willems, 2015), often with unsatisfactory results (Régny & Cathébras, 2016;Stone & Vermeulen, 2016;Sveinson, Stafánsson, & Hjaltason, 2009;Van der Feltz-Cornelis, 2015), and there is a high return rate of patients (Merkler et al, 2016). A 3-year follow-up study of 42 patients with CD/FND showed persistence in abnormal movements in more than 90% of the patients (Feinstein, Stergiopoulos, Fine, & Lang, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with FND may present acutely to the emergency department (ED) with symptoms similar to epileptic seizure, stroke, or other neurological conditions 2 . These patients often have a high return rate to the ED 3 and their symptoms have traditionally been seen as difficult to manage in the ED setting. Shorter time from symptom onset to diagnosis is an important positive prognostic factor, 4 demonstrating the importance of identifying these patients in an acute care setting.…”
Section: Introductionmentioning
confidence: 99%